Host species and environment drivers of ectoparasite community of rodents in a Mojave Desert wetlands - López-Pérez, Andrés M.; Pesapane, Risa; Clifford, Deana L.; Backus, Laura; Foley, Patrick; Voll, Ashley; Silva, Ricardo Bassini [UNESP]; Foley, Janet (Public Library of Science (PLoS), 2022)
Drivers of patterns of ectoparasitism in rodents in patchy Mojave Desert wetlands were investigated. A total of 1,571 ectoparasites in Mesostigmata, Trombidiformes, Siphonaptera and Ixodida were collected from 341 rodents (Microtus californicus scirpensis, Mus musculus, Reithrodontomys megalotis, Peromyscus eremicus, and Neotoma lepida) at eleven marshes. Trombiculids accounted for 82.5% of mites, followed by the mesostigmatid Ornithonyssus bacoti (17.5%), with chiggers predominating on voles and harvest mice. There were at least three genera of chiggers (Eutrombicula alfreddugesi, Euschoengastia sp. novel, and Blankaartia sp. novel). Fleas included Orchopeas leucopus (90.3% of all fleas) and O. sexdentatus (9.7%), and ticks were the novel endemic Ixodes mojavensis (82.1% of ticks) and Dermacentor similis (17.9%). On all hosts and at all marshes, coverage-based rarefaction sampling was over 96%, indicating coverage sufficient for analysis. Dissimilarities in ectoparasite community structure were driven mainly by chiggers, I. mojavensis and O. leucopus. Northern marshes were dominated by chiggers; central marshes by I. mojavensis; and southern marshes by O. leucopus. Primary determinants of ectoparasite community structure were host species, patch size, and parasite interspecific interactions. Host species richness and environmental factors such as patch distance and water and plant availability were not significantly associated with patterns of ectoparasitism. There were nine (60%) significant negative pairwise associations between ectoparasite taxa and no significant positive relationships. Ixodes mojavensis had the highest number of negative associations (with five other species), followed by chiggers and O. bacoti with two negative associations each. The study area is among the most arid in North America and supports numerous rare and endemic species in increasingly isolated wetland habitat patches; knowledge of ectoparasite ecology in this region identifies potential ectoparasite vectors, and provides information needed to design and implement programs to manage vector-borne diseases for purposes of wildlife conservation.